Non‐destructive lateral mapping of the thickness of the photoactive layer in polymer‐based solar cells. (30th November 2011) - Sylvester‐Hvid, Kristian O.; Tromholt, Thomas; Jørgensen, Mikkel; Krebs, Frederik C.; Niggemann, Michael; Zimmermann, Klaus; Liehr, Andreas W.
ABSTRACT Non‐destructive lateral mapping of the thickness of the photoactive layer in poly(3‐hexyl‐thiophene) : 1‐(3‐methoxy‐carbonyl)propyl‐1‐phenyl‐(6, 6)C61 (P3HT : PCBM) solar cells is demonstrated. The method employs a spatially resolved (XY) recording of ultraviolet‐visible spectra in reflection geometry at normal incidence, using a dense raster defined by a circular probe spot of 800‐µm diameter. The evaluation of the thickness of the photoactive layer at each raster point employs an algorithm‐driven comparison of the measured absorption spectrum with spectral features, as compiled from the corresponding simulated spectrum. For the robustness of the applied algorithm toward noise in the recorded absorption data to be increased, a new minimum finder algorithm is described and implemented. The thickness evaluation relies on the correct assignment of extrema in the experimental absorption spectra to the corresponding extrema in the simulated absorption spectra, and a new algorithm for this is also implemented and described. For a level of confidence for the method to be established, first thickness mapping is performed for a set of reference samples consisting of P3HT : PCBM spin‐coated on indium tin oxide‐coated float glass substrates. After this, two application examples for solar cells processed either by spin coating or slot die coating of the P3HT : PCBM layer follow. The spin‐coated solar cells have glass as the substrate with the P3HT : PCBM spun at different spinning speeds. The slot die‐coated solar cells were processed on polyethylene terephthalate foil in a roll‐to‐roll experiment involving a continuously changing P3HT : PCBM concentration along the printing direction. Copyright © 2011 John Wiley & Sons, Ltd.